Glycoproteomics of NOTCH1 EGF repeat fragments overexpressed with different glycosyltransferases in HEK293T cells reveals insights into O-GlcNAcylation of NOTCH1. (11th March 2022) - Tsukamoto, Yohei; Ogawa, Mitsutaka; Yogi, Kentarou; Tashima, Yuko; Takeuchi, Hideyuki; Okajima, Tetsuya
Abstract: O -GlcNAc modification of Notch receptors regulates Notch ligand interactions in a manner distinct from other forms of O -glycans on epidermal growth factor (EGF)-like repeats of Notch receptors. Although many proteins, besides Notch receptors, are expected to be O-GlcNAcylated by EGF domain-specific O -GlcNAc transferase (EOGT), only a small number of proteins have been reported to be modified in vivo, and elongated O -GlcNAc glycans have not been extensively explored. To extend our view of the specificity and variety of the glycan modification, we conducted a comprehensive analysis of O -GlcNAc glycans on NOTCH1 in mammals. Mass spectrometric analysis of NOTCH1 fragments expressed in HEK293T cells revealed that several EGF domains with putative O-GlcNAcylation sites were hardly modified with O -GlcNAc. Although amino acid residues before the modification site are preferentially occupied with aromatic residues, Phe and Tyr are preferable to Trp for the apparent modification with O -GlcNAc. Furthermore, a minor form of fucosylated O -GlcNAc glycans was detected in a subset of EGF domains. Fucosylation of O -GlcNAc glycans was enhanced by FUT1, FUT2, or FUT9 expression. The FUT9-dependent Lewis X epitope was confirmed by immunoblotting using an anti-Lewis X antibody. As expected from the similarity in the extended structures between O -Fuc and O -GlcNAc glycans, the Lexis X antigen was detected on NOTCH1 fragments co-expressed with L-Fringe, which mediates elongation of O -Fuc glycans. Our results refined the putative consensus sequence for the EOGT-dependent O -GlcNAc modification in mammals and revealed the structural diversity of functional Notch O -glycans.